Use of modern contraceptives on the basis of disability severity in Uganda: analysis of the 2016 demographic and health survey - Tara Casebolt; Molly Hardiman; Taylor Diaz-Leon Guerrero (Frontiers in Reproductive Health)
BackgroundWomen with disabilities have faced difficulties with accessing family planning services for decades and in many different settings. These women have both been denied access to contraception because of an inaccurate belief of the asexuality of people with disabilities and been forced or coerced into using contraceptives because of the belief they should not have children.ObjectiveThis study uses Demographic and Health Survey data to analyze the association between disability and modern contraceptive use in Uganda. A disability severity indicator was used based upon recommendations from the Washington Group on Disability Statistics.MethodsBivariate analysis was performed using chi-squares to determine if a significant association exists between modern contraceptive use and disability. Logistic regressions were run to generate odds ratios for crude adjusted models which took demographic data and covariates into consideration.ResultsDisability was not found to be significantly associated with modern contraceptive use. Women with disabilities did not have significantly different odds of using a modern form of contraceptive when compared to women without disabilities in both the crude and adjusted models.ConclusionsThese findings are inconsistent with previous studies conducted in Uganda. Additional research should be conducted to determine if there are disparities in the type of contraceptive used, sustainability of the method, and whether there is an unmet need for contraceptives. Based on the findings of this study, it is clear that women with disabilities use contraceptives. Therefore, it is essential for family planning services to be accessible to women regardless of functional limitations.